Asset management guidance for transportation agencies. - Markow, Michael J. (Research results digest (National Cooperative Highway Research Program), 2002)
This digest announces interim results from NCHRP Project 20-24(11). The digest describes three agency reports prepared by Cambridge Systematics, Inc., assisted by Parsons Brinckerhoff Quade & Douglas, Inc.; Roy Jorgensen Associates, Inc; and Paul D. Thompson. The ... reports ... are available on the NCHRP website as Web Document 41. Michael J. Markow served as the Principal Investigator.